Information management: envisioning the future libraries, Vol.I-III (Ess Ess, 2014)
Rapid advances in information processing, storage and communication technologies have revolutionized the role of the libraries and information centers all over the world. Academic research and development organizations are supported by well equipped library and information service unit to augment the objective of a parent organization. Literature explosion is the natural outcome of vast amount of research and number of users for variety of needs. The growth of digital repositories offers the prospect of extending the current scholarly communication system in order to make effective use of material that would otherwise have remained unpublished and inaccessible. With the primary objective of providing the collective information to the readers and scholars this book entitled “Information Management: Envisioning the Future Libraries” is presented. This book is an outcome of efforts of enthusiastic researchers and scholars who have submitted their scholarly research themes for publication which would help the readers to travel along with the key concepts discussed. The book is published as a set of three volumes with two chapters in the first volume, three chapters in the second volume and four chapters in the third volume. The concepts and key matters given in each chapter are clubbed logically and neatly. In the first chapter, under the theme of ‘Knowledge Organization and Processing’, stress is given on semantic web technology, XML, fuzzy neural network, knowledge management and metadata. In the second chapter, ‘Digital Libraries and E-Content Management’ emerging concepts such as digital libraries, digital preservation, virtual libraries, paperless society and e-content management are discussed in detail. ‘Web Technologies and E-Learning’ is the main theme of chapter three, in which E- Learning services, web technologies, social networks and evaluation of websites are discussed. In chapter Four entitled ‘Library Management and Marketing of Information Products and Services’ is framed as the main topic, under which informatics, marketing of information, service marketing, and financial marketing in institutional libraries are presented. ‘Innovative and Best Practices in Library and Information Science” is the core topic of the chapter five. Best practices in school, college, university libraries, web tools, assistive technologies for the disabled and public library scenario are explored in detail.